The Impact of Anemia Prevention Health Counseling on Knowledge of Pregnant Women in Puskesmas - Ellen Pesak; Jusuf Kristianto; Bongakaraeng Bongakaraeng; Johana Tuegeh; Jane Annita Kolompoy; Putri Nurul Firdaus (Syntax Corporation Indonesia, 2023)
The World Health Organization (WHO) estimates that 35-70% of pregnant women in developing countries are anemic. Indonesia is one of the developing countries with the highest incidence of anemia, which is around 70% in pregnant women. One of the causes of anemia during pregnancy is that many pregnant women do not know the prevention of anemia during pregnancy. The purpose of this study was to determine the effect of health counseling on the prevention of anemia on the knowledge of pregnant women. The research design used was pre-experimental with a one-group pretest-posttest method where the characteristics of this design were no comparison group (control). The study population was all pregnant women at the Minanga Health Center which amounted to 46 people. The sample technique used was simple random sampling, which was as many as 35 people. Analysis with Wilcoxon signed rank test. The test results have a significant influence of health counseling on anemia prevention on the knowledge of pregnant women (α ≤ 0.05, namely p-value = 0.000). The conclusion is that health counseling on the prevention of anemia increases the knowledge of pregnant women. Suggestions are expected by the puskesmas to increase counseling or education about anemia during pregnancy so that pregnant women's knowledge about anemia increases.